2014
DOI: 10.1245/s10434-014-3601-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Diametrically Polarized Tumor-Associated Macrophages in Renal Cell Carcinoma

Abstract: Intratumoral balance of diametrically polarized TAMs is a novel independent predictor for survival in patients with ccRCC. Tipping the balance toward an antitumoral phenotype might be a promising target of postoperative adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 33 publications
3
78
1
4
Order By: Relevance
“…These studies have proved the prognostic significance of TAMs in gastric cancer; however, the diametrically opposed functional status of TAMs was beyond these investigations. A recent study in renal cell carcinoma tried to prove the prognostic significance of M1/M2 phenotypes using combined analysis of CD11c and CD206 [42]. This may be better to help elucidate the prognostic significance of diametrically polarized infiltrated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have proved the prognostic significance of TAMs in gastric cancer; however, the diametrically opposed functional status of TAMs was beyond these investigations. A recent study in renal cell carcinoma tried to prove the prognostic significance of M1/M2 phenotypes using combined analysis of CD11c and CD206 [42]. This may be better to help elucidate the prognostic significance of diametrically polarized infiltrated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…37 Other authors investigated the intratumoral balance of polarized tumor-associated macrophages and showed that especially CD206/mannose receptor-positive macrophages (M2 type) are associated with reduced survival in RCC patients. 38 Recently, markers for human MDSC have been developed (e.g., CD14CHLA-DRlow) therefore the inclusion of myeloid cells in flow cytometric analyses would be a worthwhile approach in future studies. A higher amount of HLA-DRlow (CD13high) monocytes in the blood of RCC patients has been described already especially in late tumor stages 39 and might be the cause for poor results obtained with cancer vaccines of monocytederived dendritic cells.…”
Section: E985082-6mentioning
confidence: 99%
“…79 Similar results were reported for CD206, another M2 macrophage marker. 80 The expression of M2-TAMrelated genes such as those encoding CD163, IFN regulatory factor 4, and fibronectin 1 correlated with large tumor size and poor outcome, whereas expression of the iNOS gene, an M1-TAM-related gene, showed an inverse correlation. 78 We demonstrated expression of T-cell immunoglobulin and mucin domain-containing molecule-3 (TIM-3) on tumor cells and a positive correlation of CD204 + TAMs with shorter PFS in patients with RCC, 81 and we suggested that TIM-3 is implicated in resistance to antitumor therapy.…”
mentioning
confidence: 97%